The Assessment of Behaviour Intention to Use High Speed Rail (HSR) Service in Johor Among Generations Z: The Integration of PLS Structural Modelling - Abdul Hamid, Nor Aziati; Fatin Azyan Izzati Roslee,; Nabilah Huda Saleh, (Journal of Social Transformation and Regional Development, 2025)
The Kuala Lumpur-Singapore High-Speed Rail (KL-SG HSR) is a significant infrastructure project with the potential to transform regional connectivity. However, the current study of generation Z ridership in high-speed rail (HSR) services reveals a complex interplay of preferences, behaviours and socio-economic factors that influence their travel choices. While generation Z is generally characterized by a preference for sustainable and technology-integrated transport options, these trends very significantly across different countries. This nuanced understanding is essential for optimizing HSR services to cater to this demographic. Therefore, this study aimed to identify the influences of attitudes, subjective norms, perceived behaviour control, trust, and external influences towards behaviour intention to use high speed rail services among Generation Z in Johor. A total of 1845 respondents were collected using online survey. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to validate the hypotheses generated based on the fundamental theory of Technology Acceptance Model and Theory of Planned Behaviour. Key findings revealed that attitude, perceived behavioural control, and trust were the most significant predictors of behavioural intention. All constructs were significant and all the hypotheses were accepted. The findings suggest that the variables of attitude, subjective norms, price, and perceived behavioural control as the most necessary condition to be meet by the HSR operator in future prior the establishment of HSR services and building trust in the HSR project to ensure its successful implementation and long-term sustainability.